Self-Construals, Anger Regulation, and Life Satisfaction in the United States and Japan - Akutsu, Satoshi; Yamaguchi, Ayano; Kim, Min-Sun; Oshio, Atsushi (Frontiers in Psychology, 2016)
Previous studies have reported evidence that indicates differences between Western and East Asian cultures in anger regulation and its psychological consequences. However, many of these studies have focused on a specific anger regulation strategy and its relation with a psychological consequence. Here, we developed an integrated model that can comprehensively examine three different anger regulation strategies (anger suppression, expression, and control), independent and interdependent self-construals as the psychological antecedent, and life satisfaction as the psychological consequence. We estimated the model using large samples of American and Japanese adults to examine the associations between the two self-construals, three anger regulation strategies, and life satisfaction. We compared the difference in the patterns of relationships among the key constructs between the American and Japanese samples. The results confirmed previously suggested cultural differences while also discovering new culturally different paths. The results generally suggest that individual-level self-construals matter more when anger is a culturally condoned emotion (vs. condemned). The implications and limitations of the integrated model are discussed.